IMPLIKASI HUKUM ADAT TERHADAP PEMBAGIAN WARISAN ANAK PEREMPUAN PERSPEKTIF HUKUM KELUARGA ISLAM - Faizal, Liky; Nur, Efa Rodiah (Universitas Islam Negeri Raden Intan Lampung, 2022)
Lampung's indigenous peoples have a tribal culture divided into two large customary groups, namely the Saibatin and Pepadun indigenous peoples, and the majority of community members embrace Islam in terms of marital affairs, which will be passed down through the family. Indigenous peoples, in general, continue to follow the procedures outlined in their customary law. The purpose of this study is to examine the position of women in inheritance distribution in Lampung customary law in the districts of Way Kanan and Pesisir Barat through the lens of Islamic Family Law in Indonesia. This research is a field study that describes and describes the situation and phenomena that occurred in greater detail. This study investigated the role of women in inheritance distribution in depth. A qualitative descriptive research method is one in which only situations and events are described. This study does not seek or explain relationships, nor does it test hypotheses or make predictions; instead, it simply describes variables one by one. A purposive sample was used in this study. The following people participated in this study as informants: Key informants included four traditional leaders, four women who were heirs, and four indigenous people. Data was gathered through interviews, observations, and documentation, as well as primary and secondary sources. Data collection activities are carried out after the research has been completed or compiled. Data collection is one of the processes in research that can aid in the resolution of the problems being studied; thus, the data collected must be adequate. Data analysis begins with data collection and ends with data reduction, data presentation, and conclusions.